2021
DOI: 10.1152/japplphysiol.00058.2021
|View full text |Cite
|
Sign up to set email alerts
|

The balance of muscle oxygen supply and demand reveals critical metabolic rate and predicts time to exhaustion

Abstract: We tested the hypothesis that during whole body exercise, the balance between muscle O2 supply and metabolic demand may elucidate intensity domains, reveal a critical metabolic rate, and predict time to exhaustion. Seventeen active, healthy volunteers (12 male, 5 female; 32±2 years) participated in two distinct protocols. Study 1 (N=7) consisted of constant work rate cycling in the moderate, heavy, and severe exercise intensity domains with concurrent measures of pulmonary VO2 and local %SmO2 (via NIRS) on qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 52 publications
(88 reference statements)
1
18
0
Order By: Relevance
“…as a proxy for systemic pulmonary response yields far reaching possibilities for improving athletic performance, such as improving pacing strategies, simplifying performance assessment with non-invasive measures, and the potential for better understanding of central and peripheral limitations during exercise. The wider availability of affordable, portable NIRS devices that can be recorded to commercially available sport watches and cycling computers has made it more feasible for athletes, coaches, and teams to use muscle oxygenation as part of their regular training data collection ( McManus et al, 2018 ; Perrey and Ferrari, 2018 ; Kirby et al, 2021 ; Rodrigo-Carranza et al, 2021 ). Wearable NIRS devices are typically based on continuous wave (CW) NIR light technology, which despite having some technical limitations compared to more robust, non-portable NIRS equipment, introduces the significant advantages of cost reduction and portability for field applications ( Perrey and Ferrari, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…as a proxy for systemic pulmonary response yields far reaching possibilities for improving athletic performance, such as improving pacing strategies, simplifying performance assessment with non-invasive measures, and the potential for better understanding of central and peripheral limitations during exercise. The wider availability of affordable, portable NIRS devices that can be recorded to commercially available sport watches and cycling computers has made it more feasible for athletes, coaches, and teams to use muscle oxygenation as part of their regular training data collection ( McManus et al, 2018 ; Perrey and Ferrari, 2018 ; Kirby et al, 2021 ; Rodrigo-Carranza et al, 2021 ). Wearable NIRS devices are typically based on continuous wave (CW) NIR light technology, which despite having some technical limitations compared to more robust, non-portable NIRS equipment, introduces the significant advantages of cost reduction and portability for field applications ( Perrey and Ferrari, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CS (or critical power for other types of exercise) is important from a bioenergetics perspective because it separates the heavy-intensity exercise domain, within which steady-state values for pulmonary gas exchange and muscle metabolic variables can be stabilized, from the severe-intensity domain, within which such variables inexorably change over time until the exercise can no longer be tolerated (3)(4)(5)(6). During exercise performed above CS, the D´ (or W´ for other exercise modalities) is expended at a rate which is dependent on the difference between the speed being sustained and CS, and when D´ is exhausted, the highest speed that can be sustained equals CS (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 also shows a greater SmO 2 decrease in athletes with higher VO 2 max after passing the FTP and CPR breakpoint. Therefore, fatigue resistance depends on the ability to maintain critical oxygenation (CO) over time with lower SmO 2 values [19]. OC is the ability of the muscle to maintain adequate oxygen supply to match oxygen demand as the basis for steady-state exercise theory [34,36] In our study, athletes > 65VO 2 max achieved greater desaturation levels than less highly trained athletes; this is supported by Fontana et al [37], who found that the oxygen used after passing the RCP is lower and depends on the capacity for ATP production that comes from non-oxidative metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It also has a correlation with VO 2 , ventilatory thresholds and MLSS [16][17][18]. However, although there are studies that use SmO 2 during GXT to estimate ventilatory threshold points [17,18] and training zones (moderate, heavy and severe intensity) [19], there are scientific gaps regarding the physiological behaviour during SmO 2 transitions in fatmax zone, FTP, RCP and MAP. SmO 2 during fatmax, FTP and CPR relative to MMSS could differentiate the performance level of athletes, since, as a general rule, performance is a mediator of daily training planning [20].…”
Section: Introductionmentioning
confidence: 99%